A review of bottom-up and top-down emission estimates of hydrofluorocarbons (HFCs) in different parts of the world. (November 2021) - Flerlage, Hannah; Velders, Guus J.M.; de Boer, Jacob
Abstract: Hydrofluorocarbons (HFCs) are widespread alternatives for the ozone-depleting substances chlorofluorocarbons and hydrochlorofluorocarbons. They are used mainly as refrigerants or as foam-blowing agents. HFCs do not deplete the ozone layer, but they are very potent greenhouse gases, already contributing to global warming. Since 2019 HFCs are regulated under the Kigali Amendment to the Montreal Protocol, which demands reliable emission estimates to monitor the phase-down. Quantification of emissions is performed with two methods: bottom-up from product inventories or data on chemical sales; or top-down, inferred from atmospheric measurements by inverse modelling or interspecies correlation. Here, we review and compare the two methods and give an overview of HFC emissions from different parts of the world. Emission estimates reported by the different methods vary considerably. HFC emissions of developed countries (Annex I) are reported to the United Nations Framework Convention on Climate Change. These bottom-up estimates add up to only half of global emissions estimated from atmospheric data. Several studies with regional top-down estimates have shown that this gap is not owed to large-scale underreporting of emissions from developed countries, but mostly due to emissions from developing countries (non-Annex I). China accounts for a large fraction of the emissions causing the gap, but not entirely. Bottom-up and top-down estimations of emissions from other developing countries that could identify other large emitters are largely unavailable. Especially South America, West-, Central- and East-Africa, India, the Arabian Peninsula and Northern Australia are not well covered by measurement stations that could provide atmospheric data for top-down estimates. Graphical abstract: Image 1 Highlights: Widening gap between global top-down derived and reported HFC emissions is explored. Data inaccessibility and inaccurate emission factors challenge bottom-up assessment. Non-uniform geographic domains in top-down studies hinder comparison. Availability of data and measurement station coverage are globally very different. Hydrofluoroolefines begin to replace HFCs. Abstract : Plain language summary : Hydrofluorocarbons (HFCs) are a class of chemicals used in refrigerators and air conditioners, as aerosol propellant, and as fire extinguishers. HFCs are potent greenhouse gases. In 2016, the global phase-down of HFCs was agreed in the Kigali Amendment to the Montreal Protocol. To monitor the progress of these regulations, reliable estimations of regional HFC emissions are needed. HFC emissions can be estimated from statistics about production, import, export, and sales of HFCs in a country (bottom-up method) or calculated from atmospheric measurements (top-down method). Often, the results from both methods, top-down and bottom-up, do not match. For many parts of the world, not enough data is available to make bottom-up estimations and/or there are no measurement stations close enough to provide atmospheric data for top-down estimations. It is important to have more reliable information about HFC emissions and their sources to identify large emitters and prevent additional global warming caused by HFCs.